Multipurpose Trees Enrich Degraded Watershed An Approach for Rural Rehabilitation - Mishra, V.K.; Raina, J.N.; Nayak, B.K. (Journal of Soil and Water Conservation, 2022)
Watershed Management through integrated approach of Agriculture, Horticulture Dairy of Forestry" Practice, was taken up by Dr. Y.S. Parmar, University, Solan in its Horticultural Research Station at Dhaulakuan, Himachal Pradesh. Among other Forestry programines a high density plantation of three multipurpose trees i.e. Eucalyptus tereticomis, Melia azedarach and Leucaena leucocephala was established. Soil characteristics like pH, ECe, Organic Carbon, available N, P, K, exchangeable Ca and Mg are estimated to assess the soil ameliorative properties. A comparison of soil chemical characteristics between the experimental plot and the adjoining unplanted area reflected interesting informations. It was noticed that while pH and ECe depressed the status of Organic carbon, exchangeable Calcium and Magnesium, and available N.P.K. improved under plantation. Besides the optimum production of fuel-wood, fodder and small timber the soil ameliorative property of vegetation on degraded barren watershed is a suitable biological method of soil and water conservation at low cost technology.